302. Using Severe Acute Respiratory Syndrome Coronavirus-2 Spike Protein Antibody Serology in addition to the ISARIC 4C Risk Score to Better Discriminate Adverse Clinical Outcomes in Hospitalized Patients with Coronavirus Disease 2019. (15th December 2022) - Goh, Wilson; Nicholas Ngiam, Jinghao; Chhabra, Srishti; Sim, Meng Ying; Tambyah, Paul Anantharajah; Cross, Gail Brenda; Chew, Nicholas W S; Sia, Ching Hui
Abstract: Background: The Coronavirus disease 2019 (COVID-19) pandemic continues to threaten many countries globally. Large-scale vaccination exercises have helped to reduce transmission and severity of disease. We sought to modify an existing clinical score (the ISARIC-4C mortality score) to include serological status to better prognosticate hospitalized patients with COVID-19. Methods: We examined the first 1781 consecutive hospitalized patients with polymerase chain reaction (PCR) confirmed COVID-19 in a tertiary academic centre. We divided the study population into those requiring intensive care and those who did not require throughout their inpatient stay. Baseline characteristics examined include medical comorbidities, vaccination status, SARS-CoV-2 serology spike protein, duration of fever and haemodynamics were compared. Adverse outcomes were defined as patients who required intensive care or mortality. Performance of the risk scores were measured by the area under receiver operating characteristic curves (AUC) in predicting adverse outcomes. Results: The 55 patients requiring intensive care during their inpatient stay tended to have persistent fever beyond 72 hours and had lower titres of spike protein antibodies. (58.9 (±105.3) U/mL vs 144.2 (±116.2) U/mL, p = 0.007). A high spike protein antibody titre >75 U/mL was independently protective for adverse outcomes (adjusted OR 0.15, 95% CI 0.04-0.53), even after adjusting for the ISARIC-4C score and the presence of persistent fever. Adding the serological status and presence of persistent fever to the ISARIC-4C score improved its performance in predicting adverse outcomes (AUC 0.84, 95% CI 0.78-0.89). Conclusion: Addition of the SARS-CoV-2 serology spike protein titre and prolonged fever to the ISARIC-4C mortality score helps to better prognosticate adverse clinical outcomes in hospitalized patients with COVID-19. Disclosures: All Authors : No reported disclosures.